A handbook of diction for singers Italian, German, French - Adams, David 1950- (Oxford scholarship online, 2022)
Featuring updates, expansions, and a new chapter on phonetic symbols and unique sounds in Italian, German, and French, this third edition is a complete guide to achieving professional levels of diction in the three major languages of the classical vocal repertory